Website Quality Evaluation of LKP Bisma Informatika Using a Combination of Webqual 4.0, Fuzzy Analytical Hierarchy Process and Importance-Performance Analysis - Anop Sudiatmika; Gede Angga Pradipta; Roy Rudolf Huizen (Politeknik Siber Cerdika Internasional, 2026)
Background: The development of information technology has progressed significantly, consequently having an impact on the world of education in non-formal institutions such as Kursus dan Pelatihan (LKP). Websites are essential for providing information, registration, and engagement to prospective learners. However, preliminary research on the LKP Bisma Informatika website revealed that its content is still incomplete and not up to date. Objective: This research was conducted to evaluate the quality of LKP Bisma Informatika's website using an integrated approach combining WebQual 4.0, Fuzzy Analytical Hierarchy Process (FAHP), and Importance-Performance Analysis (IPA) methods, and to provide improvement recommendations. Methods: This study used a quantitative descriptive survey design, with respondents from LKP Bisma Informatika. Data were gathered through questionnaires based on three WebQual 4.0 constructs: usability, information quality, and service interaction quality. FAHP was used to determine priority weights, while IPA examined performance gaps based on user perceptions. Results: The results show that the website can be significantly improved, particularly in terms of information quality and usability. The most critical improvements needed are website speed, content accuracy, and user interface design. The integration of WebQual 4.0, FAHP, and IPA highlights a utility-based approach for providing effective recommendations to enhance the functionality of the website. Conclusion: These findings are expected to assist LKP Bisma Informatika in improving its website to better meet user needs and enhance user experience.